Listening to patients: Opportunities to improve reproductive wellness for women with chronic conditions. (17th October 2022) - Verbiest, Sarah; Cené, Crystal; Chambers, Erica; Pearsall, Marina; Tully, Kristin; Urrutia, Rachel Peragallo
Abstract: Objective: To understand how Black and Native American women with chronic conditions experience reproductive health care and identify patient‐centered strategies to improve care. Study Setting and Participants: We held a series of virtual focus groups between February 2021 and December 2021 with 34 women who self‐identified as Black or Native American, were of childbearing age, had one or more chronic conditions, and lived in North Carolina. Study Design and Analysis: This qualitative, community‐engaged study reviewed notes, video recordings, and graphic illustrations from the focus group sessions. Content analysis was used to iteratively identify themes. Emerging themes were reviewed by community and patient partners. Principal Findings: There were six thematic areas that emerged on the current state of reproductive health care for people with chronic conditions: (1) lack of trust in health care providers and institutions, (2) lack of health care provider knowledge, (3) uncoordinated care, (4) need for self‐advocacy, (5) provider bias, and (6) mental health strain from coping. Six approaches for care improvement emerged: (1) build on models of coordinated health care services from other conditions to design more comprehensive care clinics, (2) involve care coordinators or navigators, (3) improve educational materials for patients, (4) train clinicians to increase their capacity to be trustworthy and provide quality, equitable, person‐focused care, (5) design scripts to improve clinicians' ability to talk with women about infertility, miscarriage, infant loss, and (6) all interventions and research should be co‐designed to address patient priorities. Conclusions: Engaging Black and Native American patient partners with chronic conditions in research planning is feasible, necessary, and beneficial using methods that support connection, respect, and bi‐directional learning. Patient partners defined actionable strategies to improve reproductive care and wellness including comprehensive care clinics with patient navigators, trust‐enhancing interventions, and better provision of reproductive health related education.